Exercise reduces angiotensin II responses in rat femoral veins - Chies, Agnaldo Bruno; Rossignoli, Patrícia de Souza [UNESP]; Baptista, Rafaela De FÁtima Ferreira; Lábio, Roger William De; Payão, Spencer Luiz Marques (Elsevier, 2013)
The control of blood flow during exercise involves different mechanisms, one of which is the activation of the renin-angiotensin system, which contributes to exercise-induced blood flow redistribution. Moreover, although angiotensin II (Ang II) is considered a potent venoconstrictor agonist, little is known about its effects on the venous bed during exercise. Therefore, the present study aimed to assess the Ang II responses in thefemoral vein taken from sedentary and trained rats at rest or subjected to a single bout of exercise immediately before organ bath experiments. Isolated preparations of femoral veins taken from resting-sedentary, exercised-sedentary, resting-trained and exercised-trained animals were studied in an organ bath. In parallel, the mRNA expression of prepro-endothelin-1 (ppET-1), as well as the ETA and ETB receptors, was quantified by real-time PCR in this tissue. The results show that, in the presence of L-NAME, Ang II responses in resting-sedentary animals were higher compared to the other groups. However, this difference disappeared after co-treatment with indomethacin, BQ-123 or BQ-788. Moreover, exercise reduced ppET-1 mRNA expression. These reductions in mRNA expression were more evident in resting-trained animals. In conclusion, either acute or repeated exercise adapts the rat femoral veins, thereby reducing the Ang II responses. This adaptation is masked by the action of locally produced nitric oxide and involves, at least partially, the ETB- mediated release of vasodilator prostanoids. Reductions in endothelin-1 production may also be involved in these exercise-induced modifications of Ang II responses in the femoral vein.